A Bacterial Quorum Sensing Molecule Elicits a General Stress Response in Saccharomyces cerevisiae - Delago, Antonia; Gregor, Rachel; Dubinsky, Luba; Dandela, Rambabu; Hendler, Adi; Krief, Pnina; Rayo, Josep; Aharoni, Amir; Meijler, Michael M. (Frontiers in Microbiology, 2021)
Bacteria assess their population density through a chemical communication mechanism termed quorum sensing, in order to coordinate group behavior. Most research on quorum sensing has focused primarily on its role as an intraspecies chemical signaling mechanism that enables the regulation of certain phenotypes through targeted gene expression. However, in recent years several seminal studies have revealed important phenomena in which quorum sensing molecules appear to serve additional roles as interspecies signals that may regulate microbial ecology. In this study, we asked whether the budding yeast Saccharomyces cerevisiae can sense chemical signals from prokaryotes. When exposed to a variety of quorum sensing molecules from different bacterial species and from Candida albicans we found that N-(3-oxododecanoyl)-L-homoserine lactone (C12) from the opportunistic human pathogen Pseudomonas aeruginosa induces a remarkable stress response in yeast. Microarray experiments confirmed and aided in interpreting these findings, showing a unique and specific expression pattern that differed significantly from the response to previously described stress factors. We further characterized this response and report preliminary findings on the molecular basis for the recognition of C12 by the yeast.